2021
DOI: 10.1007/s00376-021-1085-z
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude, Scale, and Dynamics of the 2020 Mei-yu Rains and Floods over China

Abstract: Large parts of East and South Asia were affected by heavy precipitation and flooding during early summer 2020. This study provides both a statistical and dynamical characterization of rains and floods affecting the Yangtze River Basin (YRB). By aggregating daily and monthly precipitation over river basins across Asia, it is shown that the YRB is one of the areas that was particularly affected. June and July 2020 rainfall was higher than in the previous 20 years, and the YRB experienced anomalously high rainfal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Rainband expansion is associated with increased moisture and the northward advance of the Pacific anticyclone. Subsequently, a significant northward movement is observed around mid-June, where the rainband abruptly progressed northward to northern China and the Korean Peninsula [ 1 , 52 , 53 ]. The EASM begins to retreat after mid-August as the rainband moves southward with a relatively weaker precipitation.…”
Section: Resultsmentioning
confidence: 99%
“…Rainband expansion is associated with increased moisture and the northward advance of the Pacific anticyclone. Subsequently, a significant northward movement is observed around mid-June, where the rainband abruptly progressed northward to northern China and the Korean Peninsula [ 1 , 52 , 53 ]. The EASM begins to retreat after mid-August as the rainband moves southward with a relatively weaker precipitation.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in 2020, large regions of East Asia experienced an exceptionally wet rainy season (Figure S1b in Supporting Information S1) and intense MCS precipitation (Figure 1b), which led to severe impacts and consequential economic losses (Clark et al, 2021). In the Yangtze River Valley, 2020 was the wettest summer since 1998 (Ding et al, 2021;Volonté et al, 2021), but no significant El Niño event was observed, which is widely considered as a dominant factor at the inter-annual timescale (Liu et al, 2020;Volonté et al, 2021). Hence, it is important to see whether the MCSs over East Asia have changed in the past and whether the anomaly in 2020 may reflect part of the long-term change.…”
Section: Spatial Distributions and Linear Trends Of Mcs Precipitationmentioning
confidence: 99%
“…Remarkably, the linear trends for both MαCSs and MβCSs in these three regions are all statistically significant at the 99% confidence level. The year 2020 features the highest MCS frequency in EA and NEA, likely because of the abnormally abundant moisture transported to the Yangtze river basin (T. Chen et al., 2020; Clark et al., 2021; Ding et al., 2021; Volonté et al., 2021; L. Zhang et al., 2021) and Northeast China (Y. Liu et al., 2021) in the summer that year.…”
Section: Observed Trends In Mcs Frequency and Related Precipitationmentioning
confidence: 99%